Earnhardt Nation : The Full-Throttle Saga of NASCAR's First Family - Busbee, Jay (New York, New York : Harper, an imprint of HarperCollinsPublishers, 2016)
A profile of the influential NASCAR family is set against a backdrop of the history of the worlds fastest stock car racing organization and traces the achievements of three generations of Earnhardt drivers.
Keywords: Earnhardt, Dale, -- 1951-2001.; Earnhardt, Dale, -- Jr; Stock car drivers -- United States; Biography; Stock car racing -- United States; Biogrpahy